Development of a Spectrophotometric Assay for the Cysteine Desulfurase from Staphylococcus aureus - Emily Sabo; Connor Nelson; Nupur Tyagi; Veronica Stark; Katelyn Aasman; Christine N. Morrison; Jeffrey M. Boyd; Richard C. Holz (Antibiotics)
Background/Objectives: Antibiotic-resistant Staphylococcus aureus represents a growing threat in the modern world, and new antibiotic targets are needed for its successful treatment. One such potential target is the pyridoxal-5′-phosphate (PLP)-dependent cysteine desulfurase (SaSufS) of the SUF-like iron–sulfur (Fe-S) cluster biogenesis pathway upon which S. aureus relies exclusively for Fe-S synthesis. The current methods for measuring the activity of this protein have allowed for its recent characterization, but they are hampered by their use of chemical reagents which require long incubation times and may cause undesired side reactions. This problem highlights a need for the development of a rapid quantitative assay for the characterization of SaSufS in the presence of potential inhibitors. Methods: A spectrophotometric assay based on the well-documented absorbance of PLP intermediates at 340 nm was both compared to an established alanine detection assay and used to effectively measure the activity of SaSufS incubated in the absence and presence of the PLP-binding inhibitors, D-cycloserine (DCS) and L-cycloserine (LCS) as proof of concept. Methicillin-resistant S. aureus strain LAC was also grown in the presence of these inhibitors. Results: The Michaelis–Menten parameters kcat and Km of SaSufS were determined using the alanine detection assay and compared to corresponding intermediate-based values obtained spectrophotometrically in the absence and presence of the reducing agent tris(2-carboxyethyl)phosphine (TCEP). These data revealed the formation of both an intermediate that achieves steady-state during continued enzyme turnover and an intermediate that likely accumulates upon the stoppage of the catalytic cycle during the second turnover. The spectrophotometric method was then utilized to determine the half maximal inhibitory concentration (IC50) values for DCS and LCS binding to SaSufS, which are 2170 <semantics>±</semantics> 920 and 62 <semantics>±</semantics> 23 μM, respectively. Both inhibitors of SaSufS were also found to inhibit the growth of S. aureus. Conclusions: Together, this work offers a spectrophotometric method for the analysis of new inhibitors of SufS and lays the groundwork for the future development of novel antibiotics targeting cysteine desulfurases.